2008
DOI: 10.1140/epjc/s10052-008-0758-4
|View full text |Cite
|
Sign up to set email alerts
|

A field-theoretic model for Hodge theory

Abstract: We demonstrate that the four (3 + 1)-dimensional (4D) free Abelian 2-form gauge theory presents a tractable field theoretical model for the Hodge theory where the well-defined symmetry transformations correspond to the de Rham cohomological operators of differential geometry. The conserved charges, corresponding to the above continuous symmetry transformations, obey an algebra that is reminiscent of the algebra obeyed by the cohomological operators. The discrete symmetry transformation of the theory represents… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
153
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(157 citation statements)
references
References 43 publications
1
153
3
Order By: Relevance
“…However, these transformations have been found to be anticommuting only up to a U(1) vector gauge transformation. In our very recent works [43,44], we have derived the absolutely anticommuting set of (anti-)BRST as well as (anti-)co-BRST symmetry transformations and shown that the Abelian 2-form gauge theory is a field theoretic model for the Hodge theory. It would be very interesting to extend our present work and exploit the superfield approach to derive the above absolutely anticommuting (anti-)co-BRST symmetry transformations for the theory.…”
Section: Discussionmentioning
confidence: 99%
“…However, these transformations have been found to be anticommuting only up to a U(1) vector gauge transformation. In our very recent works [43,44], we have derived the absolutely anticommuting set of (anti-)BRST as well as (anti-)co-BRST symmetry transformations and shown that the Abelian 2-form gauge theory is a field theoretic model for the Hodge theory. It would be very interesting to extend our present work and exploit the superfield approach to derive the above absolutely anticommuting (anti-)co-BRST symmetry transformations for the theory.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out after (19) and (25), the brackets {b † , b † } = 0 and {b, b} = 0 are not produced by the pairs (s 1 , Q) and (s 2 ,Q), respectively. However, the transformations s ω (generated by Q ω ) produce all the appropriate (anti)commutators as is illustrated in (30).…”
Section: Discussionmentioning
confidence: 68%
“…We have proven that the 1D model of a rigid rotor [17], N = 2 SUSY quantum mechanical model with any arbitrary superpotential [16], N = 2 SUSY model for the motion of a charged particle under influence of a magnetic field [18], free 4D Abelian 2-form and 6D Abelian 3-form gauge theories [19][20][21], etc., are models for the Hodge theory. For all these models, we can perform the canonical quantization without taking recourse to the mathematical definition of the canonical conjugate momenta.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, within the framework of BRST formalism, that the 4D free Abelian 2-form gauge theory provides a tractable field-theoretic model for Hodge theory where de Rham cohomological operators of differential geometry and Hodge duality operation find their physical realizations in terms of the continuous and discrete symmetries, respectively [36]. Furthermore, it has also shown to be a quasi-topological field theory (q-TFT) which captures some features of Witten-type TFT and some aspects of Schwartztype TFT [37].…”
Section: Introductionmentioning
confidence: 99%